2006
DOI: 10.1063/1.2213250
|View full text |Cite
|
Sign up to set email alerts
|

Nematic-fluid structure in wall-field geometry. II. The direct correlation function

Abstract: An explicit expression for the wall-nematic direct correlation function (DCF) is obtained for any orientation of the wall with respect to an external orienting field. It is found that inside the surface of the wall, the DCF rapidly tends to a function of the nematogen orientation and depends only on parameters of the bulk fluid. We suggest that the wall-nematic DCF can be used as an ansatz for the colloid-nematic DCF in dilute nematic colloids. The reliability of this ansatz is investigated at different field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…In our previous studies we suggested that a general solution of the Ornstein-Zernike equation for a nematic fluid in the presence of a wall, arbitrarily oriented with respect to the nematic director, can be very useful for the investigation of dilute nematic colloids. In fact, we suggested using the wall-nematogen direct correlation function, obtained explicitly in [11], as an ansatz for the direct correlation function in nematic colloids. This ansatz permits explicit microscopic calculations of the density and orientational profiles, as well as potentials of mean force for large colloidal particles, such as those used in numerous experiments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous studies we suggested that a general solution of the Ornstein-Zernike equation for a nematic fluid in the presence of a wall, arbitrarily oriented with respect to the nematic director, can be very useful for the investigation of dilute nematic colloids. In fact, we suggested using the wall-nematogen direct correlation function, obtained explicitly in [11], as an ansatz for the direct correlation function in nematic colloids. This ansatz permits explicit microscopic calculations of the density and orientational profiles, as well as potentials of mean force for large colloidal particles, such as those used in numerous experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The factor 5/4 is not accidental. Formally we can take the limit of zero field (ξ → ∞) for the case of the tilted wall (from equation (17) of [11]). In this case the asymptote of the wall-nematogen total correlation function tends to a constant value at large distances from the wall,…”
Section: Corrected Ansatz For Small or Zero Fieldsmentioning
confidence: 99%
See 2 more Smart Citations
“…At long distances, this description leads to a repulsive force between a colloidal 'multipole' and its mirror image in the surface plane, closely akin to the repulsive interaction between an electrostatic multipole and an inert (nonpolarizable) wall. In the present paper, we consider wall-colloid interactions at the molecular level, applying the statistical mechanical approach used in our earlier work [8,9,[16][17][18][19][20]. We identify a different, field-dependent, wall-colloid interaction which can be attractive or repulsive depending on the particular type of anchoring at the wall and colloidal surfaces.…”
mentioning
confidence: 99%